PENGUATAN AGROFORESTRI DALAM UPAYA MITIGASI PERUBAHAN IKLIM: KASUS KABUPATEN BENGKULU TENGAH PROVINSI BENGKULU - Sri Lestari; Bambang Tejo Premono (Jurnal Penelitian Sosial dan Ekonomi Kehutanan, 2014)
The crop management systems on land owned with agroforestry system in Bengkulu Province indirectly constitutes as a form of community participation to reduce greenhouse gasses emissions. Agroforestry can be used as one of the programs in the Regional Action Plan (RAD) in an effort to mitigate and adapt to climate change. Survey methods and interviews with the community who applied agroforestry system were used to know the main purpose of the community in developing agroforestry on their land and also to determine the attitude and knowledge of the community about the role of agroforestry in mitigation and adaptation to climate change. The results showed that most of people in Central Bengkulu Regency developed agroforestry system with two or more types of plants because this pattern ismore favorable in terms of subsistence, both short and long term. From the economic side, the community developed a timber plant with the main purpose as future savings. Meanwhile, in terms of the environment, agroforestry has an important role in protecting the flora and fauna, protecting the environment, and reduce global warming. However, still many of the members of the community who have not been aware of this. Therefore, the introduction of technology and dissemination of environmental issues to the public are needed to maintain public interest in the development of agroforestry in Central Bengkulu.